Eksplorasi Etnomatematika pada Batik Mojokerto - Windi Setiawan; Yuni Listiana (Jurnal Pendidikan Matematika (JPM), 2021)
Indonesia is known as a country that has a cultural diversity. One of the cultures that needs to be maintained is batik. To preserve batik, it is not only used at the time of the gathering but by making batik as a teaching material for mathematics. one of them is Mojokerto batik. Indeed it seems strange, but there are some mathematical concepts that exist in Mojokerto batik. This type of research is qualitative research with an ethnographic approach. The researcher used an ethnographic approach because researchers were directly involved in research activities. This study aims to describe the mathematical concepts that exist in the batik. The researcher collects data by means of observation, interviews, and documentation. To test the validity of the data the researcher used triangulation of data sources. Some mathematical concepts that exist in Mojokerto batik are sets, rectangles, circles, curved lines, and folding symmetry